2018
DOI: 10.1158/0008-5472.can-18-0069
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Estrogen-Regulated MIR135A1 at 3p21.1 Promotes Tamoxifen Resistance in Breast Cancer

Abstract: The dysregulation of miRNAs has been increasingly recognized as a critical mediator of cancer development and progression. Here, we show that frequent deletion of the locus is associated with poor prognosis in primary breast cancer. Forced expression of miR-135a decreased breast cancer progression, while inhibition of miR-135a with a specific miRNA sponge elicited opposing effects, suggestive of a tumor suppressive role of miR-135a in breast cancer. Estrogen receptor alpha (ERα) bound the promoter of for its t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The genomic locus of rs57025206, 3p21, is frequently deleted in mammary carcinomas, especially in ER-negative and high-grade tumors [42][43][44] . Subsequent research has not been able to name an unequivocal cancer driver gene, even though several candidates have been suggested, including BAP1 and MIR135A 45,46 , which were detected as eQTL variants in our target gene analysis (Supplementary Data 2). However, the topological data suggested that these eQTLs might represent tissue-specific regulatory associations not present in HMEC, and that if the rs57025206related survival effect is mediated via BAP1 or MIR135A, it probably reflects host-tumor interactions.…”
Section: Discussionmentioning
confidence: 96%
“…The genomic locus of rs57025206, 3p21, is frequently deleted in mammary carcinomas, especially in ER-negative and high-grade tumors [42][43][44] . Subsequent research has not been able to name an unequivocal cancer driver gene, even though several candidates have been suggested, including BAP1 and MIR135A 45,46 , which were detected as eQTL variants in our target gene analysis (Supplementary Data 2). However, the topological data suggested that these eQTLs might represent tissue-specific regulatory associations not present in HMEC, and that if the rs57025206related survival effect is mediated via BAP1 or MIR135A, it probably reflects host-tumor interactions.…”
Section: Discussionmentioning
confidence: 96%
“…Also, discrepancies between various studies regarding e.g., the role of specific miRNA evaluated by different authors may be associated with their specific focus, demonstrating that different disease settings and study designs yield different candidates [ 74 ]. Regarding the evaluation of the likelihood of recurrence and resistance to therapeutics such as endocrine resistance [ 83 , 88 , 89 ], the expression of miRNAs should be tested in primary tumor sites, ideally in multicenter studies. Moreover, in vitro evaluation might contribute to the functional characterization of specific miRNAs [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are also very promising novel therapeutic approach to sensitize and suppress the growth of TAM-resistant tumors [ 88 ]. Zhang et aldemonstrated downregulatedexpression of miR-135a in ERα+BC cells with acquired TAM resistance; however, the overexpression of miR-135a partially resensitized cells to TAM therapy through the activation of ERK1/2 and AKT pathways and miR-135a targeted genes ESR1 , ESRRA , and NCOA1 [ 89 ]. The same principle was seen in case of miR-27 that increases the levels of ERα [ 90 ].…”
Section: Mirnas and Their Role In Endocrine Resistancementioning
confidence: 99%
See 2 more Smart Citations